KAPITAL POLITIK DALAM KONTESTASI MEMPEREBUTKAN KEKUASAAN (STUDY KASUS PEMENANGAN PASANGAN SRI HARTINI – SRI MULYANI DALAM PILKADA KABUPATEN KLATEN TAHUN 2015) - Noer Apptika Fujilestari (Jurnal Caraka Prabu, 2019)
This research reviews about how Sri Hartini – Sri Mulyani couple optimize their political capital in the winning of Klaten General Election in 2015. The triumph of Sri Hartini– Sri Mulyani has a huge political capital influence. There are some important fundamental considerations, such as: First, Sri Hartini – Sri Mulyani is a figure who is known in Klaten folk because both of them are the wife of the former Regent of Klaten. Second, Sri Hartini – Sri Mulyani is carried by the winning party of general election that is PDIP and supported by some qualify parties for general election as Nasdem, PPP, Hanura and PKS. Third, Sri Hartini – Sri Mulyani has a high financial which is strength enough. The theory which is used in this research is theory of the political Capital of Pierre Bordieu. This research uses descriptive research methods with qualitative approaching. As for the result of this research is Sri Hartini – Sri Mulyani is a couple with the highest capital accumulation than other spouses. From the four political capitals that consist of economic capital, social capital, cultural capital and symbolic capital Sri Hartini – Sri Mulyani couple has a very strong social capital than other candidate, especially in terms of the network that supports both, network of non formal and formal. PDIP as the party which brings SriHartini – Sri Mulyani is the party with the highest base mass in Klaten. in other hand, the popularity of Sri Hartini – Sri Mulyani as the wife of a former Regent of Klaten and as political figure of women who be able to take the sympathy of the citizens to choose Sri Hartini – Sri Mulyani as head of their region. The solidarity of political parties and civic organizations that support the role of klaten local elites are able to muster the mass votes to win the couple Sri Hartini – Sri Mulyani in Klaten Election 2015. Key words : political capital, ekonomic capital, social capital, cultural capital, simbolic capital.